2002
DOI: 10.1007/s00438-002-0746-6
|View full text |Cite
|
Sign up to set email alerts
|

Ovule-specific MADS-box proteins have conserved protein-protein interactions in monocot and dicot plants

Abstract: OsMADS13 is a rice MADS-box gene that is specifically expressed in developing ovules. The amino acid sequence of OsMADS13 shows 74% similarity to those of FLORAL BINDING PROTEIN 7 (FBP7) and FBP11, the products of two MADS-box genes that are necessary and sufficient to determine ovule identity in Petunia. To assess whether OsMADS13, the putative rice ortholog of FBP7 and FBP11, has an equivalent function, several analyses were performed. Ectopic expression of FBP7 and FBP11 in Petunia results in ectopic ovule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 36 publications
5
91
0
Order By: Relevance
“…It is possible that OsMADS6 interacts with other MADSbox protein(s) controlling rice flower development. In agreement with this hypothesis, OsMADS6 interacts with four SEP-like genes (OsMADS1, OsMADS5, OsMADS7 and OsMADS8), a B class gene (OsMADS16) and a D class gene (OsMADS13) in yeast cells [46][47][48]. Further genetic and biochemical analyses of the interaction of these genes with OsMADS6 will help to elucidate the mechanism of rice flower development.…”
Section: Osmads6 Is a Key Regulator Specifying Floral Organ Identitiessupporting
confidence: 56%
See 1 more Smart Citation
“…It is possible that OsMADS6 interacts with other MADSbox protein(s) controlling rice flower development. In agreement with this hypothesis, OsMADS6 interacts with four SEP-like genes (OsMADS1, OsMADS5, OsMADS7 and OsMADS8), a B class gene (OsMADS16) and a D class gene (OsMADS13) in yeast cells [46][47][48]. Further genetic and biochemical analyses of the interaction of these genes with OsMADS6 will help to elucidate the mechanism of rice flower development.…”
Section: Osmads6 Is a Key Regulator Specifying Floral Organ Identitiessupporting
confidence: 56%
“…In addition, OsMADS6 has a similar expression pattern to that of SEP genes [5,6]. Furthermore, OsMAS6 is able to form protein complexes with rice B and D proteins in yeast cells [47,48], resembling the complex formation of SEP proteins with A, B and C in Arabidopsis and other eudicot species [9,54]. Moreover, a physical interaction between BDE and ZAG1 (Zea AGAMOUS 1, a C class protein) in maize has also been shown recently [40].…”
Section: Agl6-like Genes Have a Sep-like Role In Flower Patterningmentioning
confidence: 91%
“…Similar higher order complexes were proposed for other MADS-box proteins involved in flower development (Honma and Goto, 2001), which recently led to the Quartet model for flower organ specification (Theissen, 2001). These complexes add a new dimension to the combinatorial ABCDE model and recent studies with petunia MADS-box proteins show that these interactions are conserved among angiosperm species (Favaro et al, 2002;Ferrario et al, 2003).…”
supporting
confidence: 54%
“…Yeast two-hybrid protein interaction assays showed that the petunia proteins FBP7 and FBP11 interact with the SEP-like (AGL2-like) proteins FBP2, FBP5, and FBP9 . Interestingly, the rice MADS-box protein OsMADS13 also interacts with two SEP-like proteins, OsMADS24 and OsMADS45 (Favaro et al, 2002). The evolutionary conservation of the MADS-box protein partners was confirmed by yeast twohybrid exchange assays, which showed that the protein partners of FBP7 interact with OsMADS13 and vice versa (Favaro et al, 2002).…”
Section: Evolutionary Conservation Of Stk-sep Protein Interactionsmentioning
confidence: 92%